Implementasi Sistem Informasi Monitoring Berbasis Website pada Pondok Pesantren Manba'ul Ihsan Al-Baedlowi - Lutfi Yahya; Ahmad Aftah Syukron (Lembaga Pengembangan Kinerja Dosen, 2025)
Manual data management in Islamic boarding schools often leads to inefficiencies and record-keeping errors. This study aims to design and implement a web-based monitoring information system at Pondok Pesantren Manba’ul Ihsan Al-Baedlowi to improve administrative efficiency and communication. The system was developed using the Waterfall method, which includes analysis, design, implementation, testing, and maintenance phases. Laravel framework was used due to its structured development support and strong security features. The results show that the system effectively manages student data, activity schedules, payment records, and student achievements. Blackbox testing confirmed that all features functioned as expected. The system provides easy access for administrators and parents/guardians, and supports data-driven decision-making processes. In conclusion, the developed information system is effective in improving the management process of the boarding school and is feasible for continuous implementation with regular maintenance.